2021
DOI: 10.35371/aoem.2021.33.e10
|View full text |Cite
|
Sign up to set email alerts
|

Environmental health survey for children residing near mining areas in South Gobi, Mongolia

Abstract: Background We evaluated the level and factors of heavy metal exposure to children residing in the Togttsetsii, Khanbogd, and Bayandalai soums of South Gobi province, Mongolia. Methods A total of 118 children aged 9–12 years were surveyed, and the level of heavy metal exposure in their bodies was investigated. Exposure was investigated by measuring concentrations of heavy metals such as cadmium, lead, and mercury in the blood; mercury concentration in the hair; and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the semi-arid to arid conditions of Mongolia 11 with limited water resources 12 , water pollution poses a critical risk 3,4,[12][13][14][15][16] . Insufficient scientific attention is paid to soil pollution, although mining of most minerals can be associated with soil contamination with metal(loid)s. Furthermore, there is no effective management system to assess the environmental health of mining sites 9 .In recent decades, mining areas in Mongolia have been urbanised by originally nomadic inhabitants 12 . The concentration of people in these areas may be risky due to daily exposure to potentially hazardous substances in the environment released from mining operations and stored mining waste materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the semi-arid to arid conditions of Mongolia 11 with limited water resources 12 , water pollution poses a critical risk 3,4,[12][13][14][15][16] . Insufficient scientific attention is paid to soil pollution, although mining of most minerals can be associated with soil contamination with metal(loid)s. Furthermore, there is no effective management system to assess the environmental health of mining sites 9 .In recent decades, mining areas in Mongolia have been urbanised by originally nomadic inhabitants 12 . The concentration of people in these areas may be risky due to daily exposure to potentially hazardous substances in the environment released from mining operations and stored mining waste materials.…”
mentioning
confidence: 99%
“…In the semi-arid to arid conditions of Mongolia 11 with limited water resources 12 , water pollution poses a critical risk 3,4,[12][13][14][15][16] . Insufficient scientific attention is paid to soil pollution, although mining of most minerals can be associated with soil contamination with metal(loid)s. Furthermore, there is no effective management system to assess the environmental health of mining sites 9 .…”
mentioning
confidence: 99%
“…Compared with high-income countries, there are many areas in the world where lead exposure is poorly managed, highlighting the need for a global policy to reduce lead exposure. 20 …”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the same region by Moonga et al found hot spots with mean BLLs of 519 µg/L and cold spots with mean BLLs of 70 µg/L depending on the distance from the mining site and in relation to local prevailing winds [33]. In a study conducted on 9 to 12-year-old children in Mongolia, the mean BLLs were 74.2 µg/L [34]. That is, all of the studies reported mean BLLs that were 6 to 42 times higher than those measured in the present study.…”
Section: Children Living In the Vicinity Of Mining Sitesmentioning
confidence: 92%